Odpowiedzi

Najlepsza Odpowiedź!
2010-03-09T11:00:39+01:00
X³+3x²+2x-6=0
x²(x+3)+(2x-6)=0 wtedy i tylko wtedy gdy
x=0, x=-3, lub x=3

x³+5x²+2x-8=0
x²(x+5)+(2x-8)=0 wtedy i tylko wtedy gdy
x=0, x=-5, lub x=4

x³-3x+2=0
x²(x-3)+2=0 wtedy i tylko wtedy gdy
x=0, lub x=3

-x³+3x²-3x+1=0
-x²(x-3)-(3x-1)=0 wtedy i tylko wtedy gdy
x=0, lub x=3, lub x=1/3
2010-03-09T11:03:31+01:00
X³+3x²+2x-6=0
x³+3x²+2x=6
x(x²+3x+2)=6
x=1

x³+5x²+2x-8=0
x³+5x²+2x=8
x(x²+5x+2)=8
x=1

x³-3x+2=0
X³-3x=-2
x(x²-3)=-2
x=1

-x³+3x²-3x+1=0
-x³+3x²-3x=-1
-x(x²+3x-3)=-1
x=1